Indian art - Mitter, Partha (Oxford : Oxford University Press, 2001)
"This new survey guides the reader through over 2000 years of Indian art and architecture. A rich artistic tradition is fully explored through the Hindu, Buddhist, Islamic, colonial, and contemporary periods, incorporating discussion of modern Bangladesh and Pakistan, traditional women artists, tribal artists, and the decorative arts." "Combining a clear overview with much fascinating detail, Mitter succeeds in bringing to life the true diversity of Indian culture. He discusses a wide range of examples from the influence of Islam on the Mughal court, resulting in the world-famous Taj Mahal and exquisite miniature paintings, to the nationalist and global concerns of more recent art including the rise of female artists, the stunning architecture of Charles Correa, and the vibrant contemporary art scene."--BOOK JACKET.
Includes bibliographical references, index and list of museums and websites.
Keywords: Art, Indic; Architecture -- India